Berlin Paris Bar - Müller, Heiner; Britsch, Eckart (Paris : Artcurial, Centre d'art plastique contemporain, 1991)
Attersee, Christian Ludwig ; Barfuss, Ina ; Wachweger, Thomas ; Baselitz, Georg ; Beuys, Joseph ; Broodthaers, Marcel ; Brus, Günter ; Büttner, Werner ; Castelli, Luciano ; Salomé ; Chevalier, Peter ; Dichgans, Christa ; Fetting, Rainer ; Filliou, Robert ; Graubner, Gotthard ; etc.
Berlin Paris Bar, Artcurial, Centre d'art plastique contemporain, Paris, Octobre - Novembre 1991
boek
Keywords: Berlin